The Impact of CEO characteristics on Stock Crash Price Risk: A Systematic Literature Review - Pangestuti, Rinda Siaga; Pujihastuti, Isti (AIBPM Publisher, 2024)
The purpose of this Systematic Literature Review (SLR) is to determine the effect of CEO characteristics on stock price crash risk in terms of CEO characteristics so that it can be used as a reference for potential future research directions.Â This SLR uses ROSES with VOSviewer from reference data accessed on Scopus, ScienceDirect, and Google scholar. The research results in the form of proposed hypotheses that can be used for future research include: H1: CEO physicality has a positive effect on increasing stock price crash risk; H2: CEO psychological conditions affect stock price crash risk; H3: CEO social life affects stock price crash risk; H4: Career affects stock price crash risk; H5: Demographic conditions affect stock price crash risk. The future research can be conducted in developed European countries, the US, or other developing countries, considering that most of these studies are dominated by China. The challenge in this research is access to CEO data that is private or not available on the Thomson Reuters DataStream, Capital IQ, or Bloomberg subscription.